Evaluation of Izod impact and bend properties of epoxy composites reinforced with mallow fibers - Ulisses Oliveira Costa; Lucio Fabio Cassiano Nascimento; Julianna Magalhães Garcia; Wendell Bruno Almeida Bezerra; Sergio Neves Monteiro (Journal of Materials Research and Technology, 2020)
Epoxy composites reinforced with 10, 20 and 30 vol% of a natural lignocellulosic fiber, the mallow fiber, were investigated for mechanical properties associated with Izod notch toughness and flexural resistance. For Izod tests, 150 × 120 × 10 mm plates and for three-point bend tests, 150 × 120 × 6 mm plates were fabricated in a steel mold by mixing aligned fibers with necessary percentage of diglycidyl ether of the bisphenol an epoxy resin hardened with triethylene tetramine. Each plate was kept under load of 5 ton during 24 h of curing at 25 °C. Both Izod and bend specimens were machined from corresponding plates and tested according to ASTM D256 and ASTM D790 standards, respectively. The results showed that composites with 20 and 30% of mallow fibers display a more effective reinforcement, with the predominance of fracture mechanisms, such as fiber rupture and interfacial detachment between the fibers and the matrix. The analysis of the results of both impact energies and flexural properties, was performed by the ANOVA statistics and Tukey test. Based on a 95% confidence level, the Tukey test showed that the 30 vol% of mallow fiber reinforced epoxy composites has the best performance, achieving the highest values of energy absorption, maximum flexural strength and rupture modulus. These results revealed that mallow fiber reinforced epoxy composites have promising applications as engineering materials. Keywords: Mallow fiber, Epoxy composite, Izod impact test, Ben test